Survival Strategies of the Baha'i Minority in Klaten, Central Java - Hidayat, Samsul; Sulaiman, Sulaiman (Program Studi Studi Agama Agama Fakultas Ushuluddin dan Pemikiran Islam, 2024)
The Baha'i religion originated in Persia in the 19th century and spread around the world to Indonesia, especially Klaten, Central Java. The Baha'i people in Indonesia, especially in Klaten, are classified as a minority, so they need a way to maintain their identity as an existence in religion, therefore this research discusses the survival strategy of the Baha'i people in Klaten from a cultural point of view using Kim Young Yun's thoughts on the adaptation process. This research is included in a qualitative cluster with a socio-anthropogical approach, how to collect data using direct observation, interviews and observation and data analysis using data condensation, data display and drawing conclusions. The results of this study show that the Baha'i people do adaptation not directly, a) make observations of local culture (enculturation), b) choose and determine a culture that is in harmony with the culture of the local community (acculturation), c) adapt the culture without leaving the innate culture (deculturation), and d) awareness of the importance of cultural adaptation as a solution to maintain culture and religious teachings as a religious identity (assimilation). Furthermore, the Baha'i response to local culture by using the local language, active social activities and inclusive of differences.